Regulatory changes and the volatility of stock returns – the German solar energy sector. Issue 2 (27th May 2014) - Schiereck, Dirk; Trillig, Julian
Abstract : Purpose: – The purpose of this paper is to determine the impact of political risk on the German solar energy industry. The authors analyze the period from 2006 to mid-2011, when the technological development of this sector was remarkable while the whole industry is depending on political support and subsidies. Design/methodology/approach: – The authors apply an EGARCH model assessing potential changes in conditional volatility response of solar industry stock returns following political risk events. Findings: – The results document major changes in political support of the solar industry drive capital market risk. Whereby favorable political news significantly decrease volatility response and unfavorable political news do not affect volatility response. Moreover, the authors find that the volatility response varies with the exposure to political risk. Companies with higher exposure to political risk show more significant volatility response. Practical implications: – Political risk affects the cost of capital of companies in this sector. Thus, managers are able to time equity measures in a way that they can determine periods when the investor's required return is low due to a reduced risk premium. The authors suggest risk reducing public policy facilitates investments in those industries and thus fosters the development and diffusion of immature technologies. Originality/value: – The paper helps policy makers, managers, and investors to assess the impact of political risk on the overall risk of the German solar energy sector and in a broader view of immature or high-tech industries that depend crucially on governmental support.